Food, risk and politics : scare, scandal and crisis : insights into the risk politics of food safety - Randall, Ed , 1951- (Manchester University Press ; Distributed in the United States exclusively by Palgrave Macmillan, 2009)
Food-related risks regularly grab the headlines in ways that threaten reasoned debate and obstruct sensible policy making. In this book, Ed Randall explains why that is.